(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
Kamus Dewan Perdana (KDP) (2021) is the first Malay language dictionary in the world that utilizes corpus data and websites as data sources. Big data from these various sources allow various data to be obtained and recorded in the system. Based on the given entries and literal meanings, it turns out that the use of this dictionary requires good background knowledge of the Malay language and aspects of grammar, and this is not as easy as it seems. This paper highlights some morphological issues (affixes, meanings of affixes and word classes) that seem to demand further explanation and need to be unraveled based on several selected entries found in KDP (2021). To clarify this confusion, this study also utilizes the main sources of KDP (2021), which are the fourth edition of Kamus Dewan (2016) and other main sources for word classes mentioned on page xvii. If this confusion is not resolved, the impact on users, especially students, teachers, students in institutions of higher learning, and the public, is huge. Therefore, to ensure that the Malay language continues to be sustainable, and that the dignity of the Malay language continues to be upheld and exalted, KDP (2021) must prove its authority as an authentic and certified reference for general users and not be limited to only those who have a background in Malay linguistics or a high command of the Malay language. Several of the issues that are raised in KDP (2021) and the explanations given here are expected to be referred to by general readers, and the nature of this dictionary should be understood as a recorder of Malay vocabulary and not a source for aspects of grammar. Full text: PDF